Design of a Prototype of Smoke Exhaust Control System in an Enclosed Room with the Fuzzy Sugeno Method - Setya Ardhi; Danny Kusuma; Judi Sugiono; Suhati Tjandra (Procedia of Engineering and Life Science, 2021)
Cigarette smoke can contaminate indoor air that causes some health risks. Smoke control in enclosed rooms is necessary to reduce the thick smoke in them by controlling the CO content index to the desired point. The purpose of the study, knowing the grouping of the density of smoke and the time in disposing of smoke to the point of a predetermined setpoint value of 60 ppm. This research applied the Fuzzy Logic Sugeno Method and hardware design using a prototype in the form of an acrylic box with a ratio of 1:10 of the actual size as a tool test site; LCD to display information, namely, in the form of smoke density, fan, setpoint value, and smoke value; MQ2 sensors for CO smoke detection; Arduino Nano as a microcontroller; and relay and fan as output. The experiment results resulted in 3 categories of smoke: low, medium, and high. Besides, the results of this study also showed that the time required to emit smoke in a closed room to the point of a setpoint value of 60 ppm with the help of 3 fans on each fan 12v / 0.14A is 2 minutes 05 seconds.